Analysis Of Educational Values In The Film "Children Of The Heaven - Hayati, Nursri; Hidayat, Reyhan (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
The formulation of the problem in this research is how to briefly describe the film "Children of the Heaven"; what educational values are contained in the film “Children of the Heaven”. What educational values are present in the film Children of the Heaven? The goal of this research is to discover what educational values are contained in the film Children of the Heaven. The approach used in this research is a qualitative approach with a descriptive analysis method. It was then subjected to content analysis. The findings in this study; 1) The Film was written and designed by Majid Majidi with editor H. Hasandoust and has been translated by Mas Manado in Sanana at the beginning of Ramadan in 2016/1437 H. 2) The educational values contained in the film, the first is physical education in the form of sports to make the body healthy and strong. The second is character education includes discipline, hard work, responsibility, independence. The following value is spiritual education (aqidah and morals). It is hoped that the film will help researchers understand the meaning of life and ibroh, or wisdom, so that it will serve as a valuable lesson in living life. This film also teaches the value of patience, gratitude, and sincerity